Diffuse myelitis associated with rubella vaccination. - Holt, S (1976)
Two patients who had received live rubella vaccine developed diffuse myelitis shortly afterwards. Neither patient fully recovered her motor function. In one patients the time between vaccination and development of neurological signs was rather too short to indicate definitely a causal relation. Nevertheless, the chronological association is suggestive, and other observations of such an association may strengthen the suspicion that rubella vaccination may occasionally cause severe neurological damage.